Change in the corneal material mechanical property for small incision lenticule extraction surgery - Gao, Wenjing; Zhao, Xinheng; Wang, Yan (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: To assess the distribution characteristics and related factors of stress-strain index (SSI) values and discuss changes in biomechanical parameters, including SSI, after small incision lenticule extraction (SMILE) surgery. Methods: This study included 253 patients who underwent SMILE (253 eyes). SSI and other biomechanical parameters were measured using corneal visualization Scheimpflug technology before and three months after surgery. The data collected included SSI, central corneal thickness (CCT), and eight other dynamic corneal response parameters. The Kolmogorov–Smirnov test, Pearson and partial correlation analyses, and paired-sample t-tests were used for statistical analyses. Results: Both pre-op SSI and ΔSSI follow a normal distribution, while post-op SSI does not follow a normal distribution. The decline in SSI after SMILE surgery was not statistically significant, and the data dispersion of SSI after SMILE surgery was close to that before surgery (P>0.05). No statistical correlation was noted between SSI values and age and pre-op CCT (all P>0.05). However, both pre- and post-op SSI values increased with the degree of myopia (all P<0.05) and weakly correlated with preoperative intraocular pressure and biomechanically corrected intraocular pressure (all P<0.05). Other biomechanical parameters changed significantly after surgery (all P<0.001). After SMILE, the magnitude of the deformation at the highest concave, deformation ratio, and integral radius increased significantly (all P<0.001), while ambrosio relational thickness horizontal, stiffness parameter at first applanation, and Corvis biomechanical index decreased significantly (P<0.001). Conclusions: SSI, which reflects essential corneal material attributes, differs from other corneal biomechanical parameters and remains stable before and after SMILE surgery, and can be used as an indicator to evaluate changes in corneal material properties after SMILE surgery.